PENGARUH EDUKASI PENERAPAN BUNDLE CLABSI TERHADAP PENGETAHUAN DAN KEPATUHAN PERAWAT DALAM PENCEGAHAN CLABSI PADA NEONATUS DENGAN VENA SENTRAL - Handayani, Handayani; Novikasari, Ade Ima; Roselyn, Intan Parulian Tiurma (Faculty of Nursing and Midwifery, Binawan University, 2023)
Neonates have a high risk of infection due to central venous catheter placement. One of the complications is Central Line Associated Blood Stream Infection (CLABSI). CLABSI can be prevented by applying evidence-based guidelines during installation, maintenance and removal known as the CLABSI Bundle. Evidence-based policies and training help nurses improve their knowledge and practice of central vein care. The purpose of this study was to determine the educational effect of implementing the CLABSI Bundle on the knowledge and adherence of nurses in preventing CLABSI in neonates with central veins. This type of quantitative research with a Quasi Experiment approach. The research design used a pre and posttest design without a control group. The sample of this study were 56 nurses, using the Kertjie and Morgan tables, collecting data using questionnaires and direct observation. Nurses' knowledge before being given education on the application of the CLABSI Bundle, namely having sufficient knowledge (75.0%) and after being given education had good knowledge (71.4%). Nurse compliance before being given education on the application of the CLABSI Bundle, namely the majority were obedient (76.8%) and after being given education obedience increased (91.1%). There is an effect of education on the application of the CLABSI Bundle on knowledge and nurse compliance before and after being given nursing education with the Wilcoxons test obtained pvalue: 0,000 (α:<0,05) and pvalue: 0.005 (α: <0.05). It is hoped that hospital management can facilitate regular training, carry out routine and scheduled supervision and audits so that nurses are encouraged to understand the importance of specific policies and documents used in neonates with central veins.